Assessment of the adaptive response induced by quercetin using the MNCB peripheral blood human lymphocytes assay - Oliveira, NG (2015)
Over more than two decades the existence of an adaptive response (AR) has been reported in several cell types and extensively studied with low doses of radiation. Besides radiation, some chemicals [alkylating compounds, mitomycin C (MMC), bleomycin, hydrogen peroxide and metals] may also induce an adaptive response. We have recently reported that the food mutagen quercetin can also induce an adaptive response in V79 Chinese hamster cells. In this work we have studied the effect of low doses of quercetin on the genotoxicity of MMC and bleomycin assessed by the formation of micronuclei in cytokinesis-blocked (MNCB) human peripheral blood lymphocytes. Our results suggest the existence of an AR induced by quercetin in human lymphocytes. Seven of the nine donors studied showed in at least one independent experiment a significant decrease in the frequency of MNCB induced by MMC. The range of these decreases varied between 31 and 58%. In addition, we observed an AR induced by quercetin towards challenging doses of bleomycin. In accordance with other studies with ionizing radiation in which heterogeneity of the AR in the population has been extensively observed, the response here reported also showed some degree of variability between the different donors studied. In view of the results obtained one cannot rule out a possible protective effect of low doses of quercetin leading to adaptation to further exposure to mutagens or carcinogens.